(3GdTaGAs - (3TQa Gdedc, CHh Ydj, GdQFjS GHf SjfG, GHf SjfG, GdMSjf Hf YHO Gddg Hf SjfG, J (B428(3g` (B1037(3es ((3eMeO Ydj GdLjdGfjs)
(3ChdgG (B:s
(3ChdgG(B: (3Gdaf GdSGOS ef GdLedI GdChdi aj GdefWb ef cJGH GdTaGA aj WhfjbG hgh SHY ebGdGJ, GdebGdI GdChdi aj Gdaf GdSGOS aj GdLedI GdChdi YTQ aUhds
(3BNQgG (B:s
(3BNQgG(B: (3aGfbJUQ Ydi gPG GdeHdZ aEf Pdc ZQVfG GdGSJbUGA ajeG jfJaY Hg aj GdYdhe (B. (3hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 241s
(3cTa GdXfhf, L (B2 : 1055s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs